Hijab Culture Phenomenon: Between Religion, Trend and Identity - Dewi, Eva; Amrulloh, Muhammad Afif; Suhertina, Suhertina; Sariah, Sariah; Yasnel, Yasnel (KALAM, 2022)
Hijab (headscarf) as a symbol of religion became phenomenal in the era of development of science and technology nowadays, impacting on the epistemology and axiology of hijab among Muslim women. The style of hijab used by Muslim women both artists and the general public today not only plays with hijab creations, but also clothing that is increasingly diverse, modern and fashionable. Referring the opinion of Nasaruddin Umar, the phenomenon of hijab in Indonesia is currently due to "hybridity locational "namely the dialectical result between traditional and global Western-style culture. The question that arises is whether the hijab worn by Muslim women is a symbol of godliness or simplt to follows a trend as stated above? Based on these problems, this study aims to answer these questions: 1) Why does the phenomenon of hijab arise among female students of Sunan Kalijaga State Islamic University  Yogyakarta ?. 2) What is the function of the hijab, is it a godly identity or is it just a trend? This research study is qualitative, which research procedures employed descriptive data. The respondents of this study were students of Sunan Kalijaga State Islamic University  Yogyakarta. Data collection techniques in this study are interview, observation and documentation techniques. While the data analysis technique uses descriptive analysis. The results of the study show that the causes of the phenomenon of hijab are the development of science and technology today and the increasing understanding of Muslim women about the function of using hijab in Islamic shari'a. While the function of the hijab is theological, psychological, political and fashionable.